Smart School Management System as A Student Presention Monitoring in The Khadijah High School Surabaya - Mas Nurul Hamidah (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
As a supporter of the Surabaya city government program, which will make the city of Surabaya a smart city in all aspects of the field, including in the field of education. The smart city program in Surabaya has been running in several aspects of the field, but there are still very few in the field of education, Khadijah High School is one of the schools that will implement all forms of information technology-based school management, which we can call a smart school management system. The system management method uses the RAD (Rapid Application Development) method. The expected results in making this system are, by monitoring the presence of students until end to end it can minimize student delinquency in learning.